O espaço urbano como patrimônio cultural: reflexões sobre a paisagem da Praça da República de Ijuí/RS - Cecchetto, Carise Taciane (2017)
The urban square is understood as a wide and limited by streets space composed by the grouping of architectonics and vegetation elements, turned exceptionally to the public enjoy. It also integrates in the concept of synthetic landscape, that is, a previously natural building with human interference and agency, which can show the character of landscaped architectonic patrimony for being attached to historical, socials or artistic factors of a small group or, yet, of a nation. Therefore, the landscape of Praça da República is the element of exploration of these concepts in the actual research. In this way, the study explains about Ijuí´s Praça da República as landscaped architectonic patrimony for its relevancy as historical and cultural manifestation place, for the formulation of built central landscape, for the environment and recreational attribution, as well for being the center of expansion of the urban road trace. Still, objectives primarily, to analyze the physic changes of the asset and the surroundings along the time, to verify if the central landscape has vestiges of its origin, dated back to the beginning of the colonization. The methodological approach is defined as qualitative, with exploratory character, specifically for the results and discussion chapter, the procedures for the investigation are historic and comparative. Lastly, through the portrayed history and the product attached to it, pretends to stimulate the patrimonial education and exalt the sentimental bounding of the community to this patrimony, making it recognize that this is of its property and makes part of its memory, depending the existence of a legacy, of the protective attitudes of each one and everyone togheter.